THE DEVELOPMENT OF ENTREPRENEURIAL INTENTION AMONG STUDENTS - Ilhami, Susanti Dwi; Rikah, Damayanti Rumaji (Jurnal Mebis, 2023)
The research has been purposed to describe the correlation of entrepreneurial self-efficacy and also entrepreneurial education on entrepreneurial intention by mediating the entrepreneurial mindset of students from Universitas YPPI Rembang. Students who have overtaken the Entrepreneurial Skills course become respondents to the research. A saturated sampling approach was taken in the study using 83 respondents. Data collection was obtained by distributing questionnaires. The PLS-SEM analysis method is used by researchers in answering the proposed hypothesis. The research results showed that the entrepreneurial mindset could not act as a mediating variable on the correlation of entrepreneurial self-efficacy and also entrepreneurial education on entrepreneurial intention. The findings have implications for Universitas YPPI Rembang to increase entrepreneurship education activities which are more varied so that students are more interested in building a business. Preparing a more up-to-date entrepreneurship curriculum and guest lectures by inviting more practitioners so that the business tips provided can spur the entrepreneurial intention of Universitas YPPI Rembang students.